Memahami Esensi Metode Penelitian Kuantitatif - Mustofa, Nurul Hadi; Efendi, Muhtar; Eriyanti, Ribut Wahyu; Huda, Antok Miftachul (TSAQOFAH, 2024)
Quantitative research plays a crucial role in science, providing empirical evidence and measuring phenomena objectively. However, its effectiveness is often hindered by unclear methodological presentations, particularly in terms of research design, sample selection, data collection, and statistical analysis. This article examines the main constraints affecting the clarity and credibility of quantitative scientific publications. We also explore how advancements in technology and new methodologies add to this complexity. To address these issues, we recommend the use of clearer language, systematic presentation, and improved scientific writing training as solutions. The primary aim of this article is to enhance transparency and understanding in the presentation of quantitative methods, facilitate research replication, and strengthen scientific integrity. Through this analysis, we hope to enrich the literature with strategies that researchers can adopt to refine their presentation of quantitative research methodologies.